Patients with Fontan circulation have abnormal aortic wave propagation patterns: A wave intensity analysis study. (1st January 2021) - Schäfer, Michal; Frank, Benjamin S.; Jacobsen, Roni; Rausch, Christopher M.; Mitchell, Max B.; Jaggers, James; Stone, Matthew L.; Morgan, Gareth J.; Browne, Lorna P.; Barker, Alex J.; Hunter, Kendall S.; Ivy, D. Dunbar; et al.
Abstract: Background: Elevated systemic afterload in patients with Fontan circulation may lead to impaired single ventricular function. Wave intensity analysis (WIA) enables evaluation of compression and expansion waves traveling through vasculature. We aimed to investigate the unfavorable wave propagation causing excessive afterload may be an important contributor to the overall single ventricle function and to the limited functional capacity in this patient population. Methods: Patients with hypoplastic left heart syndrome (HLHS) ( n = 25), single left ventricle (SLV) ( n = 24), and normal controls ( n = 10) underwent phase-contrast MRI based WIA analysis evaluated in the ascending aorta. Forward compression wave (FCW) representing dP/dt, backward compression wave (BCW) reflecting vascular stiffness, and forward decompression wave (FDW) representing LV relaxation were recorded and indexed to each other. Results: FCW was lowest in HLHS patients (1098 mm 5 /s), and higher in the SLV group (1457 mm5/s), and controls (6457 mm5/s) ( P < 0.001). BCW/FCW was increased in HLHS (0.22) and SLV (0.14) groups compared to controls (0.08) ( P = 0.003). Peak VO2 correlated with FCW ( R = 0.50, P = 0.015), stroke volume ( R = 0.72, P < 0.001), and cardiac output ( R = 0.44, P = 0.034). Conclusions: Patients with HLHS and SLV have unfavorable aortic WIA patterns with increased BCW/FCW ratio indicating increased systemic afterload due to retrograde compression waves. Reduced FCW and systolic MRI indices correlated with peak VO2 suggesting that abnormal systolic wave propagation may play a role in exercise intolerance for Fontan patients. Highlights: Patients with Fontan circulation have abnormal wave propagation through systemic circulation Abnormal wave propagation further elevates the single ventricle afterload Standard MRI and wave intensity indices are associated with the exercise capacity